Analysing the Speaking and Writing Competence of an Indonesian Student in the USA: A Case Study - Delvia Roza (UIR Press, 2022)
This case study is aimed to examine the communicative competence of an Indonesian student who is studying in one of the United States Universities. The evaluation of the communicative competence, such as speaking and writing, was based on the theory of Communicative Competence (CC) proposed by Celce-Murcia (2008). The spoken and written data given were from the IELTS test format. The spoken data was collected by face-to-face interview through the Skype application, while the written data was collected by sending the participant two models of the IELTS writing test, Academic and General Training model tests, through email. These data were analysed by transcribing the interview and written word-processed. It was found that the participant demonstrated strengths as well as limitation in communicative competence. It is suggested for the participant to take the opportunity to communicate with the native speakers as much as possible while he is staying in the United States. Keywords: Communicative Competence (CC), Speaking, Writing